Every dead thing - Connolly, John, 1968- (London : Hodder & Stoughton, 2010)
PI Charlie Parker, a former New York policeman, searches for the killer of his wife and daughter. Two women help him, a pretty criminal psychologist and an old Creole woman with psychic vision.
Includes a preview of the book The Reapers.
Joseph Sanders Collection.
Keywords: Parker, Charlie'Bird' (Fictitious character) -- Fiction; Private investigators -- New York (State) -- New York -- Fiction; Missing persons -- Fiction; Serial murders -- Fiction; Ex-police officers -- Fiction; Mystery; New York (N.Y.) -- Fiction; Virginia -- Fiction